DESAIN KARAKTER BERDASARKAN REKONSTRUKSI IMAJINATIF BUKU ILUSTRASI SEJARAH MASJID JAMI’ AL-ABROR SIDOARJO - Amandafira, Lailatul Azijah; Aji, Restu Ismoyo; Setiawan, Bayu (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2025)
Mosque Jami' Al-Abror, which was founded in 1678, is the oldest mosque that played an important role in the spread of Islam in Kauman, Sidoarjo. Information related to the history of the mosque and its founders is scarce; the only available source regarding the figures is oral history. To support the preservation of this history, an illustrated book was developed that also features the characters of the mosque's founders. This article focuses on the process of character design of historical figures through imaginative reconstruction. In addition to using oral history and seminar results from the 1980s as primary sources, character design is also based on historical document archives in the form of photos and paintings, as well as films set in the same time period as the mosque's founding year. These various sources provide visual references that support the accuracy of the characters, making the results more representative and relevant in depicting the founders of Jami' Al-Abror Mosque. It is hoped that this writing can serve as a reference in the preservation of local history and inspire the younger generation to better understand the history of Jami' Al-Abror Mosque